2018
DOI: 10.1037/ppm0000150
|View full text |Cite
|
Sign up to set email alerts
|

The cognitive complexity of Miss Piggy and Osama Bin Laden: Examining linguistic differences between fiction and reality.

Abstract: Is fiction a reflection of reality? Previous psychological research presents a contradicting picture. While Tetlock's value pluralism model (Tetlock, 1986) and research focused on the complexity of lying (Repke, Conway, & Houck, in press;Newman, Pennebaker, Berry, & Richards, 2003) would argue against fiction being a reflection, the concept of prototypes (Rosch, 1978) argues for it. The subsequent paper presents 2 studies that hopefully provide a clearer picture and an answer to the aforementioned question by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 35 publications
(60 reference statements)
0
27
0
Order By: Relevance
“…Consistent with this possibility, LWA in one study was significantly, but only moderately (r = .31), correlated with attitude extremity/strength on an environment-based item (Conway et al, 2018a). Conway, 2011;Conway et al, 2011) using the standardized and validated Automated Integrative Complexity system (for validation and evidence pertinent to the system, see Conway, Conway, & Houck, 2020;Houck et al, 2017;Houck et al, 2018;McCullough & Conway, 2018a, 2018bZubrod et al, 2020).…”
Section: Based Integrative Processing Than Right-wing Authoritariansmentioning
confidence: 91%
“…Consistent with this possibility, LWA in one study was significantly, but only moderately (r = .31), correlated with attitude extremity/strength on an environment-based item (Conway et al, 2018a). Conway, 2011;Conway et al, 2011) using the standardized and validated Automated Integrative Complexity system (for validation and evidence pertinent to the system, see Conway, Conway, & Houck, 2020;Houck et al, 2017;Houck et al, 2018;McCullough & Conway, 2018a, 2018bZubrod et al, 2020).…”
Section: Based Integrative Processing Than Right-wing Authoritariansmentioning
confidence: 91%
“…For instance, more recent studies comparing expert human scorers to AutoIC have shown higher correlations than the original validity paper Houck et al, 2018;McCullough & Conway, 2018a;Prinsloo, 2016). Further, there is ample evidence across various domains to suggest that AutoIC produces theoretically interpretable findings: terrorism (Houck et al, 2017;Putra et al, 2018), fictional versus real dialogue (McCullough & Conway, 2018b), decision-making (Prinsloo, 2016), the film industry (McCullough & Conway, 2018a), religion (Houck et al, 2018), and social media ( McCullough & Conway, 2019). In addition, recent tests reveal successful AutoIC replication attempts of prior hand-scored IC studies in health, ideology, and presidential leadership.…”
Section: Automated Integrative Complexitymentioning
confidence: 99%
“…AutoIC has similarly advanced our understanding of the individual stability of complex thinking (Conway & Woodard, 2019), the complexity of real versus fictional writings (McCullough & Conway, 2018a), educational interventions (Felts, 2017;Prinsloo, 2016;University of Montana Psychology Department, 2018), the popularity of movies (McCullough & Conway, 2018b), the rated quality of video game dialogue (McCullough, 2019a), the success of fan fiction (McCullough, 2020), critical response to horror films (McCullough, 2019b), and the complexity of twitter (McCullough & Conway, 2019). Thus, AutoIC has begun to offer theoretical insights into multiple important psychological arenas.…”
Section: Theoretical Contributions Of Autoicmentioning
confidence: 99%
“…At the paragraph level, the overall correlation was r = .46; for prospective tests only, the paragraph level correlation was r = .41. Since the original paper, several additional studies have also correlated expert human scorers with AutoIC across religious documents (Houck et al, 2018), comparisons of fictional versus non-fictional characters (McCullough & Conway, 2018a), decisionmaking scenarios (Prinsloo, 2016), and health (Test 3, this paper). As can be seen in Table 1, the correlations with human scorers exceeded the tests from the original validity paper in every case.…”
Section: Overlap With Expert Human Scorersmentioning
confidence: 99%